2009
DOI: 10.1007/s12273-009-9321-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the urban thermal comfort in a high density tropical city: Analysis of the proposed urban construction rules for Dhaka, Bangladesh

Abstract: The thermal comfort in urban canyons of a high density city is a very challenging issue for urban planners and designers, especially in hot humid tropical zone. The present study aims to evaluate the effects of a newly promulgated building construction rules in respect of thermal climate for Dhaka, Bangladesh, a region characterized by high density area with tropical climate. Three different urban canyons from three areas were considered which almost represents the whole city. Measurements were carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Many of the investigations provide strong evidence and findings limited to building-to-building relationships, defined as different ratios (Kakon et al, 2009;Giannopoulou et al, 2010;Hwang et al, 2011;Abreu-Harbich et al, 2013). This paper, therefore, aspires to bridge the gap in micro-climatic research related to urban design and give insight on how different urban configurations may impact temperature and wind variations.…”
Section: Uhi and Wind Flowmentioning
confidence: 99%
“…Many of the investigations provide strong evidence and findings limited to building-to-building relationships, defined as different ratios (Kakon et al, 2009;Giannopoulou et al, 2010;Hwang et al, 2011;Abreu-Harbich et al, 2013). This paper, therefore, aspires to bridge the gap in micro-climatic research related to urban design and give insight on how different urban configurations may impact temperature and wind variations.…”
Section: Uhi and Wind Flowmentioning
confidence: 99%
“…Several studies (Emmanuel and Johansson 2006;Emmanuel et al 2007;Johansson and Emmanuel 2006;Johansson et al 2013Johansson et al , 2018Kakon et al 2009;Sharmin et al 2015) have examined the influence of the urban fabric on the microclimate within urban canyons in different neighbourhoods in warm humid tropical climates. In the tropical rainforest climate of Colombo, Sri Lanka, Emmanuel and Johansson (2006) found that urban-rural temperature differences were more significant by day than by night.…”
Section: Influence Of Urban Fabric On Microclimate Variationsmentioning
confidence: 99%
“…Variations in building height play a role in creating higher turbulence around high-rise buildings, thus enhancing urban ventilation (Emmanuel et al 2007;Sharmin et al 2015). Parallel arrangement of buildings combined with setbacks to increase the distance between buildings (lowering the H/W ratio) facilitates and increases the wind speed (Emmanuel et al 2007;Kakon et al 2009). Moreover, asymmetrical aspect ratios may increase wind flow in urban canyons when tall buildings confront wind direction (Qaid and Ossen 2015).…”
Section: Influence Of Urban Fabric On Microclimate Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the CFD simulations traditionally PHOENICS [28], Fluent [20,21], CFX, and OpenFOAM [46,86] [113,114], (4) Virtual PULSE [115], and (5) Honeybee [116]. These tools have used an integrated approach to model the urban neighborhood and quantify the energy consumption of buildings in the neighborhood.…”
Section: Existing Simulation Tools and Used Field Measurementsmentioning
confidence: 99%